1996
DOI: 10.1007/bf02505818
|View full text |Cite
|
Sign up to set email alerts
|

Complete atrioventricular septal defect and ebstein anomaly

Abstract: The newborn reported here presented with congestive heart failure and cyanosis on the first day of life. Echocardiographic examination revealed complete atrioventricular septal defect and Ebstein anomaly, a rare combination that has not been previously reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…There are currently no studies on the use of ESE in the adult population with coarctation repair as the primary focus has been on the pediatric and adolescent population. These studies have found Doppler mean gradients of >30 mmHg through the descending aorta with systemic HTN during exercise suggest re-coarctation with the need of reintervention [37]. Bicycle exercise reduced systolic myocardial reserve in patients with repaired coarctation as noted by reduced isovolumic acceleration and TDI's, and diastolic reserve, as noted by TDI e' [38].…”
Section: Accepted Manuscript 16mentioning
confidence: 90%
“…There are currently no studies on the use of ESE in the adult population with coarctation repair as the primary focus has been on the pediatric and adolescent population. These studies have found Doppler mean gradients of >30 mmHg through the descending aorta with systemic HTN during exercise suggest re-coarctation with the need of reintervention [37]. Bicycle exercise reduced systolic myocardial reserve in patients with repaired coarctation as noted by reduced isovolumic acceleration and TDI's, and diastolic reserve, as noted by TDI e' [38].…”
Section: Accepted Manuscript 16mentioning
confidence: 90%